PENGENALAN HIDROPONIK MENGGUNAKAN SISTEM WICK BAGI KOMUNITAS PANDALUNGAN JEMBER - Slameto, Slameto; Rusdiana, Riza Yuli; Fariroh, Indri; Harsanti, Restiani Sih (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2023)
Gubuk Pustaka Ndalung is an alternative educational community for children and teenagers around Limbungsari Village, Ajung District, Jember Regency. Gubuk Pustaka Ndalung programs were focused on learning, playing, and creating activities. Alternative education is taught to students in formal and non-formal education. The literacy of active students in the Ndalung Library Huts about agriculture is still limited because the type of formal education provided is generally about general knowledge. Introduction to plants through hydroponic technology is important to grow a love for agriculture from an early age. The introduction and practice of hydroponic technology using a simple wick system is expected to increase students’ interest in plant cultivation and also the students' awareness of protecting the environment from waste that is difficult to degrade in the soil.